L-DOPA increases slow-wave sleep duration and selectively modulates memory persistence in older adults - Isotalus, Hanna K.; Carr, Will J.; Blackman, Jonathan; Averill, George G.; Radtke, Oliver; Selwood, James; Williams, Rachel; Ford, Elizabeth; McCullagh, Liz; McErlane, James; O’Donnell, Cian; Durant, Claire; et al. (Frontiers in Behavioral Neuroscience, 2023)
Introduction Millions of people worldwide take medications such as L-DOPA that increase dopamine to treat Parkinson’s disease. Yet, we do not fully understand how L-DOPA affects sleep and memory. Our earlier research in Parkinson’s disease revealed that the timing of L-DOPA relative to sleep affects dopamine’s impact on long-term memory. Dopamine projections between the midbrain and hippocampus potentially support memory processes during slow wave sleep. In this study, we aimed to test the hypothesis that L-DOPA enhances memory consolidation by modulating NREM sleep. Methods We conducted a double-blind, randomised, placebo-controlled crossover trial with healthy older adults (65–79 years, n = 35). Participants first learned a word list and were then administered long-acting L-DOPA (or placebo) before a full night of sleep. Before sleeping, a proportion of the words were re-exposed using a recognition test to strengthen memory. L-DOPA was active during sleep and the practice-recognition test, but not during initial learning. Results The single dose of L-DOPA increased total slow-wave sleep duration by approximately 11% compared to placebo, while also increasing spindle amplitudes around slow oscillation peaks and around 1–4 Hz NREM spectral power. However, behaviourally, L-DOPA worsened memory of words presented only once compared to re-exposed words. The coupling of spindles to slow oscillation peaks correlated with these differential effects on weaker and stronger memories. To gauge whether L-DOPA affects encoding or retrieval of information in addition to consolidation, we conducted a second experiment targeting L-DOPA only to initial encoding or retrieval and found no behavioural effects. Discussion Our results demonstrate that L-DOPA augments slow wave sleep in elderly, perhaps tuning coordinated network activity and impacting the selection of information for long-term storage. The pharmaceutical modification of slow-wave sleep and long-term memory may have clinical implications. Clinical trial registration Eudract number: 2015-002027-26; https://doi.org/10.1186/ISRCTN90897064, ISRCTN90897064.